Using of electromagnetic radiation for optimization produktion condidions of technical alcohol - Косоголова, Л. О.; Лошицький, П. П.; Коломійчук, Д. А. (Problems of Environmental Biotechnology, 2018)
The article highlights the influence of high-frequency electromagnetic radiation on yeast cells during the fermentation process. Established processing modes, in which the fermentation process is as efficiently as possible. The results of researches show that in processing of yeast cells with frequency 57–68 GHz during 7 min and at a distance of 70 mm from the source of radiation increases the activity of yeast in 2,5 times. This makes it possible to reduce the fermentation process to 2 days. Installed that the effect of irradiation is stored in the next generation of yeast, which makes it possible to reuse them.